1985
DOI: 10.1016/0749-596x(85)90021-x
|View full text |Cite
|
Sign up to set email alerts
|

Pointing and voicing in deictic expressions

Abstract: The present paper studies how, in deictic expressions, the temporal interdependency of speech and gesture is realized in the course of motor planning and execution. Two theoretical positions were compared. On the "interactive" view the temporal parameters of speech and gesture are claimed to be the result of feedback between the two systems throughout the phases of motor planning and execution. The alternative "ballistic" view, however, predicts that the two systems are independent during the phase of motor ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
0
4

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 9 publications
7
109
0
4
Order By: Relevance
“…An alternative view takes as its point of departure the fact that gestures and lexical affiliates are coordinated temporally; a finding that has been interpreted to indicate that the two behaviors have a common origin (Kendon, 1980(Kendon, , 1983MorrelSamuels & Krauss, 1991;Levelt, Richardson, & La Heij, 1985;McNeill, 1985McNeill, , 1987Schegloff, 1984). However, there is little consensus as to the locus of that common origin or the process by which gestures are transformed into articulate movements.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative view takes as its point of departure the fact that gestures and lexical affiliates are coordinated temporally; a finding that has been interpreted to indicate that the two behaviors have a common origin (Kendon, 1980(Kendon, , 1983MorrelSamuels & Krauss, 1991;Levelt, Richardson, & La Heij, 1985;McNeill, 1985McNeill, , 1987Schegloff, 1984). However, there is little consensus as to the locus of that common origin or the process by which gestures are transformed into articulate movements.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been suggested that language evolved from manual gestures: the relationship between hand and mouth begun as ingestive movements, progressively adapted for communication (Gentilucci & Corballis 2006). Others posit that gesture and speech are two different communication systems, depending upon different brain structures (Levelt et al 1985;Hadar et al 1998). The localization evidence obtained so far points to a bilateral brain network underlying gesture perception, that however includes many of the known structures in the right hemisphere that have been shown to support the perception of biological motion per se: for instance, an fMRI study by Villarreal et al (2008) demonstrated an extensive, common network underlying the recognition of gestures consisting of the right pre-supplementary motor area, the right STS/ STG, the left inferior posterior parietal cortex, and bilateral superior posterior parietal cortex (PPc), precuneus, fusiform gyri, occipitotemporal regions and visual cortices.…”
Section: Visual Modality: Lateralization Of Biological Motion Perceptionmentioning
confidence: 99%
“…There is evidence that the scope of gestural movements typically finishes at the end of intonational phrases (Loehr, 2012;Shattuck-Hufnagel et al, 2010;see Krivokapić, 2014, for a review) and that listeners can automatically extract prosodic structure by using the temporal scope of manual beat gestures and thus use these gestural features disambiguating the syntactic structure (Guella€ ı et al, 2014). Interestingly, phrase boundaries seem to impact not only the ending point of a gesture movement, but also the timing of the distinct gesture phases in relation to speech landmarks (De Ruiter, 1998;Esteve-Gibert and Prieto, 2013;Krivokapić et al, 2015;Krivokapić et al, 2016;Levelt et al, 1985). EsteveGibert and Prieto (2013) observed that the movement pattern of the manual pointing gestures mimicked that of F0 movements.…”
Section: Introductionmentioning
confidence: 99%
“…Manual gestures are by far the most-studied gestures, beat and pointing manual movements traditionally receiving most of the researchers' attention (e.g., Kendon, 1980;Leonard and Cummins, 2011;Treffner et al, 2008, for beat gestures;De Ruiter, 1998;Levelt et al, 1985;RochetCapellan et al, 2008;Roustan and Dohen, 2010, for pointing gestures). Leonard and Cummins (2011) used a motion caption system to track hand gestures while participants were reading a short fable.…”
Section: Introductionmentioning
confidence: 99%